Strategi Pengembangan Fasilitas Wisata Di Pantai Tanah Barak, Desa Kutuh, Kecamatan Kuta Selatan (Jurnal Destinasi Pariwisata, 2025)
Tanah Barak Beach, located in Kutuh Village, South Kuta District, Badung Regency, is an emerging coastal tourism destination in Bali, Indonesia. Known for its dramatic twin limestone cliffs and pristine white sands, the beach has garnered increasing attention from both domestic and international tourists. However, its tourism development remains constrained due to inadequate facilities and limited service infrastructure. This study aims to analyze the current condition of tourist facilities at Tanah Barak Beach and propose strategic directions for their improvement and development of tourism facilities. The research adopts a qualitative approach using the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis framework. Data collection was conducted through field observation, semi-structured interviews with key informants (including site managers and tourists), and documentation review. The study categorizes existing infrastructure into three types: main facilities (e.g.,hotels or lodgings, food and beverage outlets, recreational facilities), supporting facilities (e.g., parking areas, shopping or convenience stores, transh bins, public restrooms), and complementary facilities (e.g., information centers, gazebos, signage). The findings indicate a significant gap between the growing tourist demand and the readiness of available amenities, particularly in sanitation, accessibility, and recreational services. The SWOT analysis reveals the need to leverage Tanah Barak’s natural appeal while addressing infrastructure gaps, managing visitor safety, and enhancing the overall tourist experience. Strategic recommendations include community-based facility development, improved connectivity with neighboring attractions, and environmentally sensitive infrastructure planning. This research contributes to tourism studies by emphasizing the importance of facility development in shaping sustainable and competitive tourism destinations.
Keywords: Tourism Facility Development; SWOT Analysis; Tanah Barak Beach